The amplified come as you are : the story of Nirvana - Azerrad, Michael (HarperOne, 2023)
In 1993, Michael Azerrad published Come as you are: the story of Nirvana, which stands as the definitive biography of Nirvana, the legendary band that upended the pop cultural landscape with Nevermind, the landmark album that became the soundtrack of Generation X, capturing its confusion, frustration, and passion. Written with the band's complete cooperation--the only book to feature interviews with singer-guitarist Kurt Cobain, bassist Krist Novoselic, and drummer Dave Grohl--it became a massive bestseller, translated into fourteen languages. Seven months after the book's original publication, Cobain was dead by suicide, making Come as you are the only book-length record of the inner life and creative mind of one of the most significatnt songwriters and musicians in rock history. Now, Azerrad has revisited and reconsidered his original text. Vivid, evocative, and thought-provoking, this "amplified" version is a truly unique and exciting book within a book.